A positive focus to lessen the stigma: How to increase engagement in coaching. Issue 4 (1st June 2015) - Cole, Graham
Abstract : Purpose: – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: – It is often stated that the workforce is a company's most important asset. Many organizations seem to recognize this. That is perhaps why finding effective ways to develop employees occupies a prominent place on growth agendas. Various options are available where training and development is concerned. Coaching is among those growing in popularity both within firms and business education courses such as Master of Business Administration programs. It typically involves a one-to-one relationship whereby a professional coach seeks to enhance the capabilities of key personnel to benefit both individual and organizational performance. Firms clearly reap the rewards when the experience is able to help top-performers reach even greater heights. Practical implications: – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.